Pemanfaatan Serbuk Cangkang Telur Ayam dan Pupuk Kascing di Tanah Ultisol terhadap Pertumbuhan dan Produksi Terung Ungu (Solanum Melongena L.) - Afrinaldi Lubis; Syahbudin Hasibuan; Asmah Indrawati (Jurnal Ilmiah Pertanian ( JIPERTA), 2020)
This study aims to determine the growth and yield of eggplant with chicken egg shell powder utilization and Kascing fertilizer, This research was conducted from March until the month of June 2019.Â The method used in this study is a randomized block design in factorial, with 2 (two) treatment factors, namely: 1) Factors dose of powdered chicken egg shells (C), which consists of five levels, namely: C0 = control ( without treatment); C1 = chicken egg shell powder 5 g / polybag; C2 = chicken egg shell powder 10 g / polybag; C3 = chicken egg shell powder 15 g / polybag; C4 = chicken egg shell powder 20 g / polybag; 2) Factors Kascing fertilizers (K), which consists of 4 levels, namely: K0 = control (no treatment); K1 = Kascing fertilizer with a dose of 10 ton / ha (25 g / polybag); K2 = Kascing fertilizer with a dose of 20 ton / ha (50 g / polybag); K3 = Kascing fertilizer with a dose of 30 ton / ha (75 g / polybag), each treatment was repeated two (2) times so that there are 40 experimental plots. Each experimental plot consisted of 5 plants with 3 plant samples. The parameters were observed in this study consisted of plant height, leaf area, number of flowers per sample, the number of fruit per sample, production per sample, production per plot and volume of roots.Â From the research that has been done can be concluded as follows: 1) Giving powder chicken egg shells effect no significant effect on plant height, leaf area, number of flowers / sample, the number of fruit / samples, production / sample production / plot and the volume of the roots of plants eggplant; 2) Fertilizer Kascing significant effect on plant height, leaf area and production / samples as well as very significant effect on the number of fruit / samples and production / plot, but no real effect on the number of flowers / plant samples eggplant; and 3) a combination of administration of a chicken egg shell powder and fertilizer Kascing no real effect on the growth and yield of eggplant.